Continuously Generated H(2)O(2) Stimulates the Proliferation and Osteoblastic Differentiation of Human Periodontal Ligament Fibroblasts - Choe, Youngji (2012)
Numerous studies have shown that hydrogen peroxide (H(2)O(2)) inhibits proliferation and osteoblastic differentiation in bone-like cells. Human periodontal ligament fibroblasts (PLF) are capable of differentiating into osteoblasts and are exposed to oxidative stress during periodontal inflammation. However, the cellular responses of PLF to H(2)O(2) have not been identified. In this study, we examined how H(2)O(2) affects the viability and proliferation of PLF by exposing the cells to glucose oxidase (GO) or direct addition of H(2)O(2). We also explored the effects of GO on the osteoblastic differentiation of PLF and the mechanisms involved. The viability and proliferation in PLF were increased with the addition of 10 mU/ml GO but not by volumes greater than 15 mU/ml or by H(2)O(2) itself. GO-stimulated DNA synthesis was correlated with the increase in cyclin E protein levels in the cells. Osteoblastic differentiation of PLF was also ugmented by combined treatment with GO, as evidenced by the increases in alkaline phosphatase activity, mineralization, collagen synthesis, and osteocalcin content in the cells. The inductions of runt-related transcription factor 2 and osterix mRNA and proteins were further increased in PLF incubated in combination with GO compared to those in untreated cells. These results demonstrate that the continuous presence of H(2)O(2) stimulates the proliferation of PLF and augments their potential to differentiate into osteoblasts through the up-regulation of bone-specific transcription factors. Collectively, we suggest that H(2)O(2) may elicit the functions of PLF in maintaining the dimensions of the periodontal ligament and in mediating a balanced metabolism in alveolar bone.